Pengaruh Pendidikan Seksual Terhadap Pengembangan Sikap Berkomunikasi Bagi Siswa Sekolah Menengah - Vitalis Djarot Sumarwoto (Jurnal Pendidikan, 2010)
Considered under the development path, students of secondary school belong to the 3rd phase of 14 up to 21 years of age plunging in teenager’s period. The teenager’s period has attracted many experts’ attentions which is then assumed as the period of sexual maturity. For educators, this period becomes an interesting focus of study viewed through other aspect, rather than sexual maturity. Socio-psychologically, this period brings them into broader interaction with adults. They do not belong to the subordinate class as children anymore; rather they interact horizontally with adults. Radical change experienced by youngsters in periode of puberty often results in bewilderment which negatively entails curiousity to peform sexual conducts. Such evidence should be viewed educationally as a problem which needs to be cleared up. They urgently need educational hands to lead their curiousity to the proper end. The education is carried out to serve the needed information, knowledge and understanding all about sexual life so as to perform the proper and healthy sexual conducts. The assumption the writer proposes is that there is a significance enfluence of sex education towards the positive communication on teenagers.